Thariqah al-Sam'iyyah wa al-syafahiyyah fi sharf: Tathbiquha, Tahaddiyatuha wa Hilluha - Maulana, Muhammad Rifqi; Shodiqin, Rahmat; Nasrulloh, Harits (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to find out the implementation of the sam'iyah wa shafahiyyah method in sharf learning at Ma'had Bakkah Martapura, where initial observations showed students' difficulties in tashrif, particularly in translating the concept of time. For example, the sentence â€œAku meminta ampunâ€ (I ask for forgiveness) is sometimes translated incorrectly using fi'il madhi or fi'il mudhori', which can interfere with students' understanding of the meaning and proper use of fi'il in different contexts. This study is a qualitative research with descriptive narrative method. The research subjects were 4 sharf teachers and the students. The object of the research is the implementation of the sam'iyah wa shafahiyyah method. Data collection techniques used observation, interviews, and documentation. Data analysis was done by data reduction, data presentation, and conclusion drawing. The results showed three main stages: planning (lesson plans, objectives, materials), implementation (routine activities, muroja'ah, tashrif practice, punishment), and evaluation (process and learning outcomes). The findings indicate the need for further emphasis on understanding the concept of time in sharf learning. Further research can be conducted to develop more effective learning strategies.